KOMUNIKASI ANTARPRIBADI ORANG TUA MENCEGAH KEKERASAN VERBAL PADA ANAK DI RT 012/ RW 001 DUSUN KAYANGAN DESA BALAM JAYA KECAMATAN BALAI JAYA KABUPATEN ROKAN HILIR - Nadia Dwi Santika; Achiriah Achiriah; Abdul Rasyid (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, dan Pendidikan, 2023)
This research is entitled "Interpersonal Communication of Parents Preventing Verbal Violence in Children in RT 012 / RW 001 Kayangan Hamlet, Balam Village Jaya Sub district Balai Jaya Rokan Hilir Regency". The purpose of this research is to find out what verbal violence the child is doing, how interpersonal communication of parents to prevent verbal violence in children and what are the obstacles for parents to prevent verbal violence in their children. obstacles parents prevent verbal violence in RT 012 / RW 001 Hamlet Kayangan Village Balam Jaya Sub-district Balai Jaya Rokan Hilir Regency. To obtain answers to the problem formulations in this study, the researcher used Newcomb's ABX theory. using Newcomb's ABX theory. This research method is a descriptive qualitative method. The results of this study indicate that verbal violence that children verbal violence that children do, namely saying harsh words, berating, and insulting others. To parents' interpersonal communication to prevent verbal violence in children is done with two-way or direct communication and it is done at times. with two-way or direct communication and it is done at certain times only so that the interpersonal communication carried out by parents is carried out by parents. certain times only so that interpersonal communication carried out by parents related to the efforts to prevent verbal violence in children have not run optimally. The obstacles for parents to prevent verbal violence are lack of time, lack of response from the child when invited to communicate. response from the child when invited to communicate and a bad environment.